Trabalho de equipa em saúde como processo de relação formal potenciador da satisfação e motivação laboral - Jeremias, Ana Teresa Nogueira; Correia, Pedro Miguel Alves Ribeiro (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
Team health work is widely used but remains a challenge and its consequences on job satisfaction and motivation are ambiguous. In order to minimize this uncertainty, a systematic review of the literature was carried out with eighteen journals from five scientific databases. In general, it was concluded that the evidence is still limited, but the summary data of medium to high-quality publications allow team work, essentially collaboration, to be recognized as a process of formal relationship between workers enhancing satisfaction and motivation.